Fabrication and characterization of micro/nano filter for isolation of waterborne pathogens - Majid Ebrahimi Warkiani (2012)
Water plays a central role in our lives, and access to safe and clean water is essential for each person. Life-threatening diseases caused by some waterborne pathogens such as Cryptosporidium parvum oocysts are largely associated with contaminated drinking water supply. The C. parvum oocysts contamination level of concern in drinking water is far below the sensitivity of most current detection technologies, such as flow cytometry, immunological methods or polymerase chain reaction assays (PCR). Therefore, development of a rapid and effective method for concentration of C. parvum oocysts present in a large volume of drinking water is critical for accurate detection and quantification. Microfiltration techniques have been widely used for isolation and recovery of C. parvum oocysts from water samples. However, negative features of commercial filters such as rough surface, tortuous pore path and low pore density can severely compromise their efficiency and lower their throughput during microfiltration. To address these issues, micro-fabrication techniques have been employed in this thesis work to develop novel isopore membranes, which contain pores with the same size and shape for ultra-fast filtration of waterborne pathogens from large volume of water samples. In this context, three important characteristics of micro-fabricated membranes (i.e., high throughput, high recovery ratio and low turbidity of eluent) were addressed and appropriate experiments for proving these hypotheses performed. In addition, the advantage of micro-fabricated membranes with identical pore sizes as a promising tool for studying the fouling phenomenon for different pore geometries is demonstrated. The application of transparent polymeric membranes as a useful tool for direct observation through the membrane (DOTM) is also shown. Lastly, design and fabrication of an automated filtration system for isolation and recovery of waterborne pathogens is presented. Results of some preliminary genetic tests using a fully integrated bio-chip are also depicted.